A social network analysis of the goal scoring passing networks of the 2016 European Football Championships - Mclean, S.; Salmon, P. M.; Gorman, A. D.; Stevens, N. J.; Solomon, C. (Human Movement Science, 2018)
In the current study, social network analysis (SNA) and notational analysis (NA) methods were applied to examine the goal scoring passing networks (GSPN) for all goals scored at the 2016 European Football Championships. The aim of the study was to determine the GSPN characteristics for the overall tournament, between the group and knock out stages, and for the successful and unsuccessful teams. The study also used degree centrality (DC) metrics as a novel method to determine the relative contributions of the pitch locations involved in the GSPN. To determine changes in GSPN characteristics as a function of changing score line, the analysis considered the match status of the game when goals were scored. There were significant differences for SNA metrics as a function of match status, and for the DC metrics in the comparison of the different pitch locations. There were no differences in the SNA metrics for the GSPN between teams in the group and knock out stages, or between the successful and unsuccessful teams. The results indicate that the GSPN had low values for network density, cohesion, connections, and duration. The networks were direct in terms of pitch zones utilised, where 85% of the GSPN included passes that were played within zones or progressed through the zones towards the goal. SNA and NA metrics were significantly different as a function of changing match status. The current study adds to the previous research on goal scoring in football, and demonstrates a novel method to determine the prominent pitch zones involved in the GSPN. These results have implications for match analysis and the coaching process. AUTORREFERAT